MIDDLE-UPPER MIOCENE VOLCANIC ASHES OF THE KERCH-TAMAN REGION - Rostovtseva Yu.V.; Parfenova O.V. (My University, 2006)
Results of the detailed study of Miocene volcanic ashes from Kerch and Taman peninsulas are presented. Based on the distribution of pyroclastics in the rocks under consideration, the Sarmatian and late Meotian stages of volcanic activity are distinguished. In close association with other geological data, results of the first microprobe analysis of the volcaniclastic materials are analyzed. It has been revealed that Sarmatian ashes are characterized by rhyolitic composition, whereas upper Meotian ashes correspond to dacites and rhyodacites. Decrease of silicate content and increase of alkalinity in the studied pyroclastic rocks are traced from ancient to younger sediments. The upper Meotian volcanics are noted for higher concentration of potassium. The predominantly vitroclastic Kerch-Taman ashes with a low content of calcium and high contents of potassium and sodium most likely belong to a single magmatic center. Stages of volcanic events and petrochemical similarity of composition of the magmatic products suggest that the studied ash material belongs to volcanic centers of the Lesser Caucasus. © Pleiades Publishing, Inc. 2006.
Keywords: Miocene; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Миоцен